The invention of science why history of science matters for the classroom - Milne, Catherine (Catherine Elizabeth) (SensePublishers, 2011)
The invention of science: why history of science matters for the classroom introduces readers to some of the developments that were key for the emergence of Eurocentric science, the discipline we call science. Using history this book explores how human groups and individuals were key to the invention of the discipline of we call science. All human groups have a need and desire to produce systematic knowledge that supports their ongoing survival as a community. This book examines how history can help us to understand emergence of Eurocentric science from local forms of systematic knowledge. Each chapter explores elements that were central to the invention of science including beliefs of what was real and true, forms of reasoning to be valued, and how the right knowledge should be constructed and the role of language. But most importantly this book presented these ideas in an accessible way with activities and questions to help readers grapple with the ideas being presented.